A case of idiopathic hypogonadotropic hypogonadism with dental and orofacial defects: A key to the perception of possible molecular etiology - Adity Bansal; Prashant Kumar Verma; Rahul Bhakat; Ashi Chug; Srinivas Gosla Reddy (Wolters Kluwer Medknow Publications, 2022)
Isolated deficiency of gonadotropin-releasing hormone is a heterogeneous disorder with wide genetic and clinical overlap. It mainly presents as hypogonadotropic hypogonadism (HH). HH associated with anosmia is known as Kallmann syndrome (KS), while its normosmic variant is called normosmic idiopathic HH. However, it is associated with several nonreproductive features including dental defects. Fibroblast growth factor receptor 1 gene mutation, which is seen in the autosomal dominant form of idiopathic HH (HH 2), has often been linked to the associated dental abnormalities and orofacial defects; however, no literature exists for its association with anosmin-1 (ANOS1) gene mutation which is found in the X-linked form of HH (KS). ANOS1 gene was earlier known as KAL1 (Kallmann syndrome 1) gene, and encodes for the extracellular matrix protein called anosmin. Hence, we report a case of idiopathic HH (KS) so as to delineate the possible role of ANOS1 gene in dental/orofacial development. This can help prioritize gene screening and also provide scope for further genetic studies required to prove such association.